(untitled) (Journal of the College of Languages (JCL), 2024)
Translation is a dynamic and living process that cannot be considered equal to the original text and requires the appropriate structure, language, thought and culture of the target language, and the translator’s intellectual, linguistic and cultural influences inadvertently penetrate into the translated text. It causes heterogeneity of the destination text with the source text. Admiral’s theory is trying to help by providing components and suggested approaches to resolve these inconsistencies. In the meantime, in addition to the mission of putting words together, the translator must sometimes sit in the position of the reader and judge and evaluate the translated text in order to understand its shortcomings and try to correct it and adapt the text to the text as much as possible. Pay the destination language. Jean-René Ladmiral, a famous French theorist, enumerates the components to face translation problems that the translator should know and act on. This destinationist theorist believes that it is incorrect to limit translation to simple decoding and that translation should be accompanied by rewriting and the translator should produce meaning or re-create it. This research is trying to investigate the effectiveness of Admiral’s theory in translation from Arabic to Persian with a descriptive and analytical method. The present research has investigated the translation of Arabic texts into Persian based on Admiral’s theory, which is considered a new research in terms of comprehensiveness and can be a specific and accurate basis for translations in which reproduction is important. چکیده ترجمه فرایندی پویا و زنده است که نمی‌توان آن را تماماً برابر با متن اصلی قلمداد کرد و ساختار، زبان، اندیشه و فرهنگی مناسب با زبان مقصد را می‌طلبد و به صورت ناخواسته عوامل تاثيرگذار فکری، زبانی و فرهنگی مترجم در متن ترجمه رسوخ پيدا مي‌کند و باعث ناهمگونی متن مقصد با متن مبدأ مي‌گردد. نظریه لادمیرال در تلاش است با ارائه مؤلفه‌ها و رویکردهای پيشنهادی در جهت رفع این ناهمگونی‌ها کمک کند. در این بين، مترجم علاوه بر ماموریت قرار دادن کلمات کنار یکدیگر، باید گاهی در جایگاه خواننده نيز بنشيند و به قضاوت و ارزیابی متن ترجمه شده بپردازد تا کمی‌ها و کاستی آن را درک کند و درصدد اصلاح آن و مناسب سازی هرچه بيشتر متن با متن زبان مقصد بپردازد. ژان رنه لادمیرال، نظریه پرداز نامدار فرانسوی، مؤلفه‌هایی را برای رویارویی با مشکلات ترجمه برمی‌شمارد که مترجم می‌بایست آنها را بشناسد و به آنها عمل کند. این نظریه‌پرداز مقصدگرا معتقد است که محدود نمودن ترجمه به رمزگردانی ساده نادرست است و ترجمه باید با بازنویسی همراه باشد و مترجم در آن به تولید معنا یا آفرینش مجدد بپردازد. این پژوهش در تلاش است با روش توصیفی،‌تحلیلی به بررسی کارآمدی نظریه لادمیرال در ترجمه از عربی به فارسی بپردازد. پژوهش پيش‌رو به صورت موردی ترجمه متون عربی به فارسی را بر پایه نظریه لادمیرال بررسی نموده که از حيث جامعيت، پژوهشی جدید به حساب می‌آید و می‌تواند مبنایی مشخص و دقيق برای ترجمه‌هایی باشد که بازآفرینی در آن اهميت دارد. Received on 27/9/202 Accepted on 7/11/2023 Published on 2/1/2024